New economic model and Universiti Sains Malaysia’s APEX strategy. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2010)
The engagement of Universiti Sains Malaysia (USM) with globalisation in its role as the pre-eminent higher educational institution in Malaysia has entailed a radical rethink in respect of how USM engages the competitive higher educational market place. While the USM strategy could be viewed in part as a recognition of some of the inevitabilities of contemporary global higher educational competition it also entails a strong critique of neo-liberalism and the ‘cultural imperialism’ that is at the root of neo-liberal globalisation. USM’s strategy is predicated on several critical assumptions/insights.